The fault in our stars [book club bag] - Green, John, 1977- (Dutton Childrens Books, 2012)
Despite the tumor-shrinking medical miracle that has bought her a few years, Hazel has never been anything but terminal, her final chapter inscribed upon diagnosis. But when a gorgeous plot twist named Augustus Waters suddenly appears at Cancer Kid Support Group, Hazel's story is about to be completely rewritten.